Physiological arousal guides situational appraisals and metacognitive recall for naturalistic experiences. (10th February 2023) - Stasiak, Joanne E.; Mitchell, William J.; Reisman, Samantha S.; Gregory, David F.; Murty, Vishnu P.; Helion, Chelsea
Abstract: As individuals navigate the world, they are bound to have emotionally intense experiences. These events not only influence momentary physiological and affective responses, but may also have a powerful impact on one's memory for their emotional experience. In this research, we used the naturalistic context of a haunted house to examine how physiological arousal is associated with metacognitive emotional memory (i.e., the extent to which an individual remembers having experienced a certain emotion). Participants first navigated the haunted house while heart rate and explicit situational appraisals were recorded, and then recalled specific events from the haunted house and the intensity of these affective events approximately one week later. We found that heart rate predicted both the intensity of reported scariness in the haunted house and meta-cognitive memory of affect during recall. Critically, we found evidence for malleability in metacognitive emotional memory based on how the event was initially labeled. Individuals tended to recall events that they explicitly labeled as fear-evoking as being more intense than they reported at the time of the event. We found the opposite relationship for events that they labeled as not fear-evoking. Taken together, this indicates that there are strong relationships between physiological arousal and emotional experiences in naturalistic contexts, but that affective labeling can modulate the relationship between these features when reflecting on the emotionality of that experience in memory. Graphical abstract: Image 1 Highlights: Naturalistic paradigm examined real-time physiological responding and situational appraisal. Participants navigated a haunted house while undergoing heart rate sampling and affective appraisals. Physiological arousal positively predicted situational appraisals of scariness. Physiological arousal also predicted metacognitive recall of emotional experience. Metacognitive emotional memory was systematically biased based on how the event was labeled.